Enzootic Bovine Leukosis in Italy: Epidemiological Issues after Free Status Recognition and Measures Applied to Tackle the Last Persistent Clusters - Cecilia Righi; Carmen Iscaro; Stefano Petrini; Roberto Lomolino; Francesco Feliziani (Pathogens, 2021)
Enzootic Bovine Leukosis (EBL), caused by the bovine leukemia virus (BLV), has been eradicated in over 20 countries, most of which are in Western Europe. The European Commission, in 2017, declared Italy to be an officially EBL-free country by means of Commission Implementing Decision (EU) 2017/1910, despite the presence of some infection clusters located in four regions of Central-Southern Italy. As a consequence of persisting infection, the Italian Ministry of Health established specific eradication measures in these areas. In collaboration with the National Reference Laboratory for the Study of Ruminant Retroviral Infectious Diseases, the Ministry of Health employed data from the veterinary information system digital platform, combined with a gap analysis exercise, to monitor and verify the progress of control activities within infection clusters during the period 2018–2021. Our aim was to identify any remaining gaps and, consequently, specific measures to eliminate the factors favouring EBL persistence, on the basis of a description and analysis of the current data regarding epidemiological trends in Italian clusters. The final goal is to achieve the implementation of a less expensive surveillance plan in these areas, as well. The results of comprehensive analysis showed that the eradication activities had been effectively implemented by official local veterinary services, resulting in a drastic reduction of EBL outbreaks in most territories during the period 2018–2021.